On the limited usefulness of comparative politics modelling for understanding VET systems - Frommberger, Dietmar [Verfasser]; Porcher, Christoph [Verfasser] (My University, 2025)
„In comparative VET research, a model developed from the perspective of comparative politics, the so-called ‘skill formation systems typology’ developed by Busemeyer and Trampusch, dominates the discourse. However, models to compare VET systems often rely on a narrow set of assumptions and fail to account for their complexity. We therefore review this typology and highlight its limitations. This article argues that this typology has limited usefulness for understanding vocational education and training (VET) systems. We advocate for a approach from the perspective of vocational education studies that takes into account the unique contexts and characteristics of specific VET systems. The article concludes that there is a need for substantively robust and valid distinctions based on appropriate models that allow for the international comparison of VET systems.“ (authors’ abstract; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S System beruflicher Bildung; 370; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Modellierung; Typologie; Vergleich